2013
DOI: 10.1371/journal.pone.0059421
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Association between TNF-α −308G>A Polymorphism and Type 2 Diabetes Mellitus in Han Chinese Population

Abstract: ObjectiveA meta-analysis was applied to evaluate the associations between tumor necrosis factor-α (TNF-α) −308G>A (rs1800629) polymorphism and type 2 diabetes mellitus (T2DM).MethodsHardy-Weinberg equilibrium (HWE) was employed to test genetic equilibrium among the genotypes of the selected literature. Power analysis was performed with the Power and Sample Size Calculation (PS) program. A fixed or random effect model was used on the basis of heterogeneity. Publication bias was quantified and examined with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 30 publications
(24 reference statements)
3
23
0
9
Order By: Relevance
“…Sensitivity analysis was performed by omitting each study in turn to assess the stability of the outcomes. 17 Funnel plot was used to perform the publication bias. In addition, a subgroup analysis by region was performed.…”
Section: Efficacy Of Surgical Treatment For Ldh S Ji Et Almentioning
confidence: 99%
“…Sensitivity analysis was performed by omitting each study in turn to assess the stability of the outcomes. 17 Funnel plot was used to perform the publication bias. In addition, a subgroup analysis by region was performed.…”
Section: Efficacy Of Surgical Treatment For Ldh S Ji Et Almentioning
confidence: 99%
“…At the functional level, it has been reported that the A allele of rs1800629 increases the transcriptional rate of the gene [10,23,24]; additionally, this same polymorphism has been associated with different diseases, such as hepatic cirrhosis [25], gastritis, gastric cancer [26], Type 2 diabetes mellitus [27] and inflammatory-autoimmune diseases, such as ankylosing spondylitis [28], systemic lupus erythematosus [29] and rheumatoid arthritis [30]. With regard to respiratory diseases, Kumar et al found an association between the same polymorphism and bronchial asthma in an Indian population [31].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with T2DM are at increased risk of other diseases including cardiovascular disease, kidney failure, blindness, neuropathy, and peripheral circulatory disease. T2DM thus has a significant impact on the quality of life of the patient, and increases the morbidity and mortality of other diseases (Liu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%